Species structure of the ephemeroids of the regional park of local importance «Nemyriv Pobuzhia» near the village of Hvozdiv - Shevchuk, Oksana; Kryklyva, Svetlana; Shevchuk, Victoria; Khodanitska, Olena; Tkachuk, Olesya; Vergelis, Victoria (ScienceRise: Biological Science, 2020)
Analyzing the literature data, it was found, that the majority of ephemeroids that grown in the territory of Ukraine are directly or indirectly influenced by humans, which leads to accelerated rates of decrease in their number. Urban factors influence not only the species structure of populations, but also their absolute quantitative indicators. The purpose of the research was to study the floristic composition of ephemeroid plants in the territory of a landscape park of local importance «Nemyrivske Pobuzhya» near the village of Gvozdiv, Nemyriv, district of Vinnytsia region. Materials and methods. The study of the floristic composition of ephemeroid plants in the territory of the landscape park of local importance "Nemyrivske Pobuzhzhya" was carried out by the expedition-route method, as well as by the accidental-regulatory method - laying of accounting sites with an area of 1 m2. The systematic identification of plants was determined using a designator. The abundance of species was determined by the Gult-Drude scale (with the addition of A. Uranov and P. Yaroshenko). The meeting coefficient (%) was determined by the formula: R = a x 100 / n. Results. It was revealed, that on the territory of Nemyrivske Pobuzhya the structure of the ephemeroid plants includes 27 species of plants, belonging to 19 genus, 14 families, 12 orders and 2 classes. Such orders as Ranunculales (7 species or 25.9 % of the total ephemeroid species), Papaverales (4 species or 14.8 %), Liliales (4 species or 14.8 %), Amaryllidales (3 species or 11.1%), Capparales (2 species or 7.4 %) are represented by the largest number Anemone sylvestris L., Ficaria verna L., Viola odorata L., Galanthus nivalis L. were dominant among the species. Conclusions. It was established, that Galanthus nivalis L. is one species that is growing at the researched area and registered in the IUCN Red List of Threatened Species; and two species (Allium ursinum L. and Galanthus nivalis L.), included in the «European Red List». 6 species of ephemeroids are included in the Red Book of Ukraine: Leucojum vernum L., Allium ursinum L., Galanthus nivalis L., Crocus reticulatus Stev. ex Adams., Pulsatilla grandis Rupr. and Pulsatilla pratensis L. (Mill). 4 species of plants have the status of rare plants of regional importance: Anemone sylvestris L., Dentaria bulbifera L., Dentaria quinquefolia M. Bieb. and Primula veris L.